Digital-Based Internationalization Strategy In Penetrating The Global Market: A Case Study On Footwear MSMes in Mojokerto - Arif Isnaini; Sudarmiatin; Heri Pratikto (Abadi Institute, 2026)
This research aims to analyze the digital-based internationalization strategy implemented by